Race and workplace discrimination: The mediating role of cyber incivility and interpersonal incivility. Issue 3 (25th July 2019) - Daniels, Shanna; Thornton, LaDonna M.
Abstract : Purpose: Drawing upon theories of modern discrimination, the present study focuses on cyber incivility and interpersonal incivility as mechanisms through which race leads to perceived discrimination. Participants included 408 full-time working adults who responded to an online survey. The results indicate that Non-White employees experience subtle forms of discrimination through the use of e-mail, which accentuate the need for organizations to eradicate workplace mistreatment so that their employees can avoid the adverse outcomes associated with experiencing cyber incivility. The purpose of this paper is to extend the understanding of selective incivility and concludes with directions for future research and practical implications. Design/methodology/approach: Participants included 408 full-time working adults who responded to the survey online. Findings: The results indicate that race was indirectly associated with discrimination through cyber incivility. The results indicate that Non-White employees experience subtle forms of discrimination through the use of technology and cyber space which accentuate the need for organizations to eradicate workplace incivility so that their employees can evade the adverse outcomes associated with experiencing incivility at work. Research limitations/implications: This study extends the understanding of selective incivility and concludes with directions for future research and practical implications. Originality/value: This paper is the first to explore the relationship between race, cyber incivility and discrimination.